Oxr1 is essential for protection against oxidative stress-induced neurodegeneration. - Oliver, P; Finelli, M; Edwards, B; Bitoun, E; Butts, D; Becker, E; Cheeseman, M; Davies, K; Davies, B (Public Library of Science, 2011)
Oxidative stress is a common etiological feature of neurological disorders, although the pathways that govern defence against reactive oxygen species (ROS) in neurodegeneration remain unclear. We have identified the role of oxidation resistance 1 (Oxr1) as a vital protein that controls the sensitivity of neuronal cells to oxidative stress; mice lacking Oxr1 display cerebellar neurodegeneration, and neurons are less susceptible to exogenous stress when the gene is over-expressed. A conserved short isoform of Oxr1 is also sufficient to confer this neuroprotective property both in vitro and in vivo. In addition, biochemical assays indicate that Oxr1 itself is susceptible to cysteine-mediated oxidation. Finally we show up-regulation of Oxr1 in both human and pre-symptomatic mouse models of amyotrophic lateral sclerosis, indicating that Oxr1 is potentially a novel neuroprotective factor in neurodegenerative disease.